Michael Clayton [videorecording (DVD)] - Pollack, Sydney, 1934-2008; Gilroy, Tony; Clooney, George; Wilkinson, Tom, 1948-2023; Swinton, Tilda; Pollack, Sydney, 1934-2008; O'Keefe, Michael, 1955-; Elswit, Robert, 1950-; Howard, James Newton; Edwards, Sarah (Costume designer) (Bros. Entertainment Inc., 2008)
Michael Clayton is an in-house fixer at one of the largest corporate law firms in New York. A former criminal prosecutor, Clayton takes care of the law firm Kenner, Bach, & Ledeen's dirtiest work at the behest of the firm's co-founder, Marty Bach. Burned out with his job as a fixer, his divorce, a failed business venture, and mounting debt have left Clayton inextricably tied to the firm. At U/North, meanwhile, the career of litigator Karen Crowder rests on the multi-million dollar settlement of a class-action suit that Clayton's firm is leading to a seemingly successful conclusion. But when Kenner Bach's brilliant and guilt-ridden attorney Arthur Edens sabotages the U/North case, Clayton faces the biggest challenge of his career and his life.